Mapping Current Trend Of Nursing Service Quality Research In Indonesia (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Nursing service quality (NSQ) is the cornerstone of high-impact care, strengthening healthcare systems, and showcasing the highest standards of professional excellence. This systematic literature review (SLR) aims to explore the current NSQ literature within the Indonesia context by examining research trends, theoretical frameworks, key concepts, and future directions. 137 articles published between 2009 and 2024 in the Scopus database was systematically screened and anlized using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The analysis identified five major research streams: nursing practice and patient care, quality of life and patient-centered outcomes, hospital management and healthcare systems, emerging healthcare challenges, and pandemic response. Four key antecedents of NSQ were identified: staffing and resources, training and competencies, leadership and administration, and health system infrastructure, along with four core elements: interpersonal care, crisis response, practice competence, and support systems. The analysis also highlights four primary consequences of NSQ: patient outcomes, nurse well-being, social impact, and organizational performance. Future research should focus on workforce well-being, leadership and organizational dynamics, patient safety and ethical standards, and integrated, population-specific nursing care. These insights provide a strategic roadmap for advancing NSQ research and practice in Asia.
Keywords: Service quality; Nursing service quality; Systematic literature review